ANALISIS SOAL UJIAN BIOLOGI SEMESTER I SISWA KELAS X SMA NEGERI 1 KINALI KABUPATEN PASAMAN BARAT TAHUN PELAJARAN 2013/2014. - Kesuma, ELSA Okta (STKIP PGRI Sumbar, 2014)
Analysis of items is an activity that can help improve the test quality. This research is aimed to provide information about validity, reliability, difficulty index, discrimination power and affectiveness options on items of the biological examination in first semester at X class at SMAN 1 Kinali in West Pasaman district in academic year 2013/2014. This research is a descriptive research in which the researcher describes the results of the items analysis in first semester at X class in Biology subject. From the data analysis, it can be concluded that the validity (0,34) is in the low criteria, the reliability (0,89) is in the high criteria, the difficulty index (0,38) is in the adequate criteria, discrimination power (0, 17) is in the bad criteria. Effectiveness options with effective option key (31 items), ineffective option key (19 items), rapscallion effective option (8 items), rapscallion ineffective option (42 items). In terms of validity, reliability, difficulty index, discrimination power and effectiveness options, there are 8% meet with good criteria and 92% do not meet with good criteria.